Design of RGD–ATWLPPR peptide conjugates for the dual targeting of αVβ3 integrin and neuropilin-1. Issue 22 (18th May 2018) - Thoreau, Fabien; Vanwonterghem, Laetitia; Henry, Maxime; Coll, Jean-Luc; Boturyn, Didier
Abstract : A dual targeting system provides an enhanced tumour-to-background ratio. Abstract : Targeting the tumour microenvironment is a promising strategy to detect and/or treat cancer. The design of selective compounds that co-target several receptors frequently overexpressed in solid tumours may allow a reliable and selective detection of tumours. Here we report the modular synthesis of compounds encompassing ligands of αV β3 integrin and neuropilin-1 that are overexpressed in the tumour microenvironment. These compounds were then evaluated through cellular experiments and imaging of tumours in mice. We observed that the peptide that displays both ligands is more specifically accumulating in the tumours than in controls. Simultaneous interaction with αV β3 integrin and NRP1 induces NRP1 stabilization at the cell membrane surface which is not observed with the co-injection of the controls.